COGNITIVE BEHAVIORAL THERAPY FOR HOARDING DISORDER: A META‐ANALYSIS. Issue 3 (14th January 2015) - Tolin, David F.; Frost, Randy O.; Steketee, Gail; Muroff, Jordana
<x xml:space="preserve">Abstract</x> Background Hoarding disorder (HD) is a new diagnosis in DSM‐5 (American Psychiatric Association, 2013). Cognitive‐behavioral therapy (CBT) appears promising for the treatment of HD, and has been tested in both individual and group settings. Methods The present study used meta‐analytic techniques to examine the overall strength of effect of CBT on HD, as well as on its component symptoms (clutter, difficulty discarding, and acquiring) and associated functional impairment. Potential demographic and treatment‐related moderators of CBT response, as well as the presence of clinically significant change were also examined. From 114 published articles, 10 articles comprising 12 distinct HD samples (N = 232) met inclusion criteria and were retained for analysis. Results HD symptom severity decreased significantly across studies with a large effect size. The strongest effects were seen for difficulty discarding, followed by clutter and acquiring. Functional impairment showed the smallest effect in the moderate range. Female gender, younger age, a greater number of CBT sessions, and a greater number of home visits were associated with better clinical outcomes. Reliable change was found in the majority of samples for each outcome domain. Rates of clinically significant change, however, were lower (percentage ranged from 24 to 43). Thus, in most cases, study patients' post‐treatment scores remained closer to the HD range than to the normal range. Conclusions CBT is a promising treatment for HD, although there is significant room for improvement. Results are discussed in terms of treatment refinement for HD, and additional moderator variables are suggested for further study.